عادة زواج المسافة: دراسة فقهية تحليلية = The custom of distant-marriage: a juristic analytical study - Mahmud Osman, Halimo; Mat Jubri@Shamsuddin, Mustafa (IIUM Press, International Islamic University Malaysia, 2018)
This research presents a marriage custom called the custom of "Distant-Marriage," where the guardian is intentionally excluded during the marriage contract without any necessary reason that called for it. The researchers discuss about legal marriage and its conditions which include (according to the sound view of Muslim jurists,) the consent of the guardian. The researchers also mention the different opinions of jurists concerning this guardianship during the marriage contract, followed by the evidence of each School of Islamic Law and then state the fairest opinion on the matter. In addition, the researchers mention the pillars of marriage, its rulings, and its purposes because of which it has been legislated. All of this is mentioned as an introduction to the main subject of the research. Then the researchers move to talk about the crux of the subject which is "Distant-Marriage" with its definition, and the reasons that facilitated its spread among Muslims. The researchers then speak about the effects and damages caused by “Distant-Marriage,” including the large number of divorces, the displacement or homelessness of children and the separation between relatives and family members. Finally, the researchers talk about the position of Shafi'ī School of Law on “Distant-Marriage” indicating that this marriage is not related to this School of Law. Therefore, the researchers state that “Distant-Marriage” violates the method of Islamic legal marriage, and that Muslims must avoid it.